The Moon is Down Movie Still - Twentieth Century Fox Film Corporation:::Creator::::::::::::
Four men stand with their arms raised, surrendering to Germans. From left to right: unknown actor, Doctor Albert Winters (Lee Cobb), unknown actor, and Mayor Orden (Henry Travers.) RESTRICTED USE